Future Control and Automation Proceedings of the 2nd International Conference on Future Control and Automation (ICFCA 2012) - Volume 2 - Deng, Wei.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This volume Future Control and Automation- Volume 2 includes best papers from 2012 2nd International Conference on Future Control and Automation (ICFCA 2012) held on July 1-2, 2012, Changsha, China. Future control and automation is the use of control systems and information technologies to reduce the need for human work in the production of goods and services. This volume can be divided into six sessions on the basis of the classification of manuscripts considered, which is listed as follows: Mathematical Modeling, Analysis and Computation, Control Engineering, Reliable Networks Design, Vehicular Communications and Networking, Automation and Mechatronics.
Mathematical Modeling, Analysis and Computation -- Control Engineering -- Reliable Networks Design -- Vehicular Communications and Networking -- Automation and Mechatronics -- Automation and Mechatronics.
Keywords: Engineering; Computer engineering; Engineering; Robotics and Automation; Control; Electrical Engineering